A constituição da subjetividade em raps dos Racionais MC's - Moreira, Tatiana Aparecida (2009)
The objective of this dissertation is to investigate the composition of subjectivity in “Nothing like a day after another” (“Nada como um dia após o outro dia”), the 2002 Rational Mc’s group double-CD (grupo Racionais MC’s). In order to reveal this subjectivity by means of analysis of the rap discourse genre, some concepts proposed by Bakhtin (1976[1926], 1995[1929], 2003[1979]) are methodologically used: dialogism, active responsive attitude, intonation (tune). Besides these bakhtinian conceptions, which represent the theoretical basis for this research, other notions are also evoked as Maingueneau’s (1997[1987], 2004[1998], 2005, 2006, 2008) and Amossy’s (2005) proposal of discursive ethos, together with the notion of style adopted by Granger (1974[1968]) and Possenti (2001a[1988], 2001b), as well as the articulations between style and ethos discussed by Discini (2003, 2008) and Mussalin (2008). Thus, the analysis focuses on the dialogic responsive position of the speakers in relation to themselves and to their interlocutors, specially the “trout” (o “truta”) and the “lands” (“senhor de engenho”). Subjectivity may be found within the rap-songs by means of indicators (GINZBURG, 2002[1989]) presented when data is analysed. These initial data show that subjectivity shows up in the dialogic process in which the “I” maintains with the “other”, the “brother” and the “master of property”. Thus, the “I” becomes the “other” – of which it is composed, and vice versa.